Axial Behaviour of Slender RC Circular Columns Strengthened with Circular CFST Jackets - Yiyan Lu; Tao Zhu; Shan Li; Weijie Li; Na Li (Advances in Civil Engineering)
This paper investigates the axial behavior of slender reinforced concrete (RC) columns strengthened with concrete filled steel tube (CFST) jacketing technique. It is realized by pouring self-compacting concrete (SCC) into the gap between inner original slender RC columns and outer steel tubes. Nine specimens were prepared and tested to failure under axial compression: a control specimen without strengthening and eight specimens with heights ranging between 1240 and 2140 mm strengthened with CFST jacketing. Experimental variables included four different length-to-diameter (L/D) ratios, three different diameter-to-thickness (D/t) ratios, and three different SCC strengths. The experimental results showed that the outer steel tube provided confinement to the SCC and original slender RC columns and thus effectively improved the behavior of slender RC columns. The failure mode of slender RC columns was changed from brittle failure (concrete peel-off) into ductile failure (global bending) after strengthening. And, the load-bearing capacity, material utilization, and ductility of slender RC columns were significantly enhanced. The strengthening effect of CFST jacketing decreased with the increase of L/D ratio and D/t ratio but showed little variation with higher SCC strength. An existing expression of load-bearing capacity for traditional CFST columns was extended to propose a formula for the load-bearing capacity of CFST jacketed columns, and the predictions showed good agreement with the experimental results.